2022
DOI: 10.1111/tgis.12971
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning method for creating globally applicable population estimates from sentinel data

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Vargas-Munõz et al (2022) applied a Markov random fields (MRF) method that iteratively enhances the initial estimations of a dasymetric disaggregation method. Fibaek et al (2022) followed a deep learning approach to generate daytime and nighttime population estimates at 10 m resolution using satellite imagery, structural area estimates, and structure classifications. The spatial disaggregation method introduced by Monteiro et al (2018Monteiro et al ( , 2019Monteiro et al ( , 2021 iteratively refines estimates generated by pycnophylactic interpolation or dasymetric mapping, by applying different types of regression models.…”
Section: Spatial Disaggregation With Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Vargas-Munõz et al (2022) applied a Markov random fields (MRF) method that iteratively enhances the initial estimations of a dasymetric disaggregation method. Fibaek et al (2022) followed a deep learning approach to generate daytime and nighttime population estimates at 10 m resolution using satellite imagery, structural area estimates, and structure classifications. The spatial disaggregation method introduced by Monteiro et al (2018Monteiro et al ( , 2019Monteiro et al ( , 2021 iteratively refines estimates generated by pycnophylactic interpolation or dasymetric mapping, by applying different types of regression models.…”
Section: Spatial Disaggregation With Machine Learningmentioning
confidence: 99%
“…Fibæk et al. (2022) followed a deep learning approach to generate daytime and nighttime population estimates at 10 m resolution using satellite imagery, structural area estimates, and structure classifications. The spatial disaggregation method introduced by Monteiro et al.…”
Section: Related Workmentioning
confidence: 99%
“…We call this kind of practices spatially explicit machine learning (Janowicz et al, 2020;Li et al, 2021;Mai, Jiang, et al, 2022;Yan et al, 2017Yan et al, , 2019. Some of the unique challenges include how to represent different types of spatial data into the embedding/subsymbolic space , how to achieve geographic generalizability for a given machine learning/deep learning model (Goodchild & Li, 2021;Li et al, 2022), how to perform transfer learning across space and tasks (Fibaek et al, 2022), how to avoid geographic biases in GeoAI models , and so forth. This special collection also includes two innovative articles that tackle two questions we mentioned above.…”
Section: Subsymbolic Geoai: Spatially Explicit Machine Learningmentioning
confidence: 99%
“…The fourth article, from Fibaek et al (2022), presents a deep learning model for population estimation in areas geographically distinct from Northern Europe. The two major contributions of this article are as follows: (1) the authors demonstrate how to use the same deep learning architecture and transfer learning to solve three tasksstructure area prediction, structure type classification, and population prediction for Ghana and Egypt based on Sentinel data; (2) the authors show how to use multi-sensor data to produce high-resolution population estimation for both daytime and nighttime, using deep learning.…”
Section: Subsymbolic Geoai: Spatially Explicit Machine Learningmentioning
confidence: 99%
“…Examples of direct future projections for gridded population distributions might not be available yet in the literature, but ML has been applied for projecting built-up land based on time series of remote sensing observations [50] and for estimating existing urban structures [7] and population density [44,122,115,132]. These approaches have demonstrated that ML can assist the extraction of information from unstructured, remote sensing data and provide effective solutions for socio-demographic issues.…”
Section: Benefits Of Machine Learning For Fine-grained Population Est...mentioning
confidence: 99%